Mechanical Performance of Mortar with Partial Replacement of Cement by Laterite Stone Powder - Moh Hari Febriana Gani; Bachtiar Aidulghani; Agung Pangestu; Tira Roesdiana (Equivalent: Jurnal Ilmiah Sosial Teknik, 2025)
Background: Cement is a key component in mortar production due to its calcium-rich composition, which plays an essential role in pozzolanic reactions. However, the extensive use of cement contributes to high carbon emissions and limestone exploitation. The incorporation of laterite stone powder as a partial cement replacement offers a potential alternative to enhance mortar performance while promoting sustainable construction practices. Aims: This study aims to evaluate the effect of laterite stone powder as a partial substitute for cement on the compressive strength and density of mortar. Methods: A quantitative experimental approach was employed through laboratory testing. Laterite stone powder passing a 200-mesh sieve was used as a partial cement replacement at substitution levels ranging from 0% to 10% by weight of cement. The mortar mixture was prepared with a cement-to-sand ratio of 1:3 and a water–cement ratio of 0.5. Compressive strength and density tests were conducted on 50 mm × 50 mm × 50 mm cube specimens at curing ages of 7, 14, 21, and 28 days. Result: The results showed that the highest compressive strength, reaching 20.33 MPa, was obtained at a 3% laterite stone powder substitution after 28 days of curing. Substitution levels exceeding 3% resulted in a gradual decrease in compressive strength, indicating a reduction in mortar performance at higher replacement ratios. Conclusion: The study concludes that laterite stone powder can be effectively utilized as a partial cement replacement in mortar at an optimum level of 3%. This substitution not only improves compressive strength but also contributes to sustainable construction by reducing cement consumption and minimizing limestone exploitation in Indonesia.